2019
DOI: 10.12965/jer.1938224.112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of muscle strengthening on perceived pain and static knee angles in young subjects with patellofemoral pain syndrome

Abstract: The purpose of this pilot study was to determine the effects of strength training of the knee muscles on perceived pain and static knee angles in young subjects with patellofemoral pain syndrome (PFPS). Ten patients, 100% female (mean age, 18.2±3.8 years), with unilateral PFPS (anterior knee pain for at least 3 months), received muscle strengthening of the hip and knee (10 sessions over a period of 3 weeks). The outcome measures were perceived pain (visual analogue scale, VAS) and static knee angles (knee rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…They were recruited from the waiting list in Rheumatology and Rehabilitation Department. The initial diagnosis was established combining medical records by CT or MRI and the presence of anterior knee pain [ 14 , 18 ]. Patients were included in this study if the following criteria were fulfilled: onset of pain longer than 3 months; positive clinical signs of PFPS (i.e., retro patellar pain, crepitation, pain in patellar grinding, direct patellar compression); no history of physical therapy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They were recruited from the waiting list in Rheumatology and Rehabilitation Department. The initial diagnosis was established combining medical records by CT or MRI and the presence of anterior knee pain [ 14 , 18 ]. Patients were included in this study if the following criteria were fulfilled: onset of pain longer than 3 months; positive clinical signs of PFPS (i.e., retro patellar pain, crepitation, pain in patellar grinding, direct patellar compression); no history of physical therapy.…”
Section: Methodsmentioning
confidence: 99%
“…The exclusion criteria were previous knee surgery, previous meniscal or ligamentous injuries, or musculoskeletal disorders. Subjects with a lower limbs dissymmetry, with cardiac or vision dysfunctions, or neurologic (whether central or peripheral) which can influence quadriceps circumference, were also excluded from the present study [ 14 ]. All participants were subjected to MRI and U/S studies of the anterior compartment of the thigh with all experimental procedures conducted in the physical therapy research lab of the hospital from 2017 to 2019 (Retrospective study).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of evidence indicates that clinicians could influence the strength, flexibility, and stability deficits in patients with PFP through a targeted exercise program [16][17][18][19]. A recent study reported that, although 34% of patients responded to a general multimodal exercise program, over 70% of patients recovered after targeted treatment based on their individual deficits [20].…”
Section: Introductionmentioning
confidence: 99%
“…Compensatory muscular adaptations are observed in such patients due to inefficient muscle activities which leads to muscle weakness, joint instability and altered limb loading where gait alterations are produced by maladaptive musculoskeletal responses [11,18]. Vastus Medialis Obliquus (VMO) muscle plays an important role in controlling the contact area and pressure distribution in patello-femoral joint [3]. It originates from medial side of the femur and inserts in quadriceps tendon.…”
mentioning
confidence: 99%